(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Today that Islamic banking industry showing an average growth rate of 17%-20% annually and comprises around 400 institutions in 75 countries, with an asset under management ranging between US 1.66-2.1 trillion, with expectations of market size to be 3.4 trillion by end of 2018 (Ernst & Young), according to Standard & Poor’s Ratings Services the potential market is 4 trillion worldwide, therefore this can be a tool for enhancing economic development in India. India is thriving, but Indians are not. With growing Islamic Banking and Indian socio-economic problems, this paper is going to find the growth of Islamic banking worldwide and will try to find out how Islamic banking can provide great opportunities to invigorate the Indian economy with the participation of previously excluded Muslims in Shariahcompliant banking and at the same time could lead to substantial inward investment to boost India’s further development. Furthermore it investigates the implementation of the Islamic banking system in India.